Numerical simulations and experimental studies on the formability of drawing quality steel in single point incremental forming / Zeradam Yeshiwas and A. Krishniah - Yeshiwas, Zeradam; Krishniah, A. (Universiti Teknologi MARA, 2021)
Based on numerical simulation and experimental studies the process parameter optimization on the formability using a 1 mm thickness Drawing Quality Steel(CR2) in Single Point Incremental Forming (SPIF)was studied. The sample shape chosen was the hayperbolic cone and fabricated using different parameter leveles. A model of numeric simulation was developed in ABAQUS explicit and then experimentally verified using a CNC milling machine. The influence of three significant control factors, namely tool radius, feeding rate, and step depth on the formability was studied. Optimization of process parameters was conducted using the L9 Taguchi orthogonal array. For optimal formability, to assess the optimum combination of process parameters, a signal noise (S/N) ratio was used. The percentage contribution of the method parameters to formability was determined by the Study of Variance (ANOVA). The findings of the study indicated that the depth of the step followed by feed rate and tool radius, was the dominant factor influencing formability. Furthermore, a good agreement between the numerical simulation and experimental study was seen. The study based on the Taguchi configuration of the study shows that at a feed rate (A2) 1000 mm/min, with tool radius (B1) 8 mm, and with step depth (C2) 0.8 mm, the optimal conditions for maximum formability were achieved.